2018
DOI: 10.1055/s-0038-1626737
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Functional Outcomes after Multiligament Knee Reconstruction

Abstract: Objectives: Although dislocation of the knee is rare, the high-energy nature of most injuries often results in high morbidity and sometimes limb-threatening injury. Literature regarding knee dislocations tends to focus upon management. There is a lack of research investigating quality of life for patients having undergone multi-ligament knee reconstruction. The purpose of our study was to review quality of life and functional outcomes as well as examine preoperative variables that may affect these outcomes for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…study reported worse ML-QOL scores in patients undergoing early reconstruction than those operated with delay. 19 In our study, we had no case of early presentation, and all the reconstructions had been performed within an average of 17.31 months or 519 days after injury. A couple of studies have investigated the results of late surgical reconstruction in patients with MLKIs.…”
Section: Discussionmentioning
confidence: 88%
“…study reported worse ML-QOL scores in patients undergoing early reconstruction than those operated with delay. 19 In our study, we had no case of early presentation, and all the reconstructions had been performed within an average of 17.31 months or 519 days after injury. A couple of studies have investigated the results of late surgical reconstruction in patients with MLKIs.…”
Section: Discussionmentioning
confidence: 88%
“…Of the 31 publications, 5 of these 4 , 5 , 8 , 48 , 52 did not report the timing from injury to surgical repair/reconstruction of the cruciate ligaments. Based on each study’s stated mean time to surgery, 10 studies ∥ reported outcomes for acute surgical intervention, 8 studies 1 , 3 , 14 , 26 , 30 , 34 36 reported outcomes for delayed surgical intervention, and 8 studies 16 , 32 , 38 , 39 , 41 , 53 , 57 , 58 included outcomes on both. According to sex distributions and male-to-female ratios, all but 2 studies 1 , 48 reported that men represented the majority in each cohort of patients.…”
Section: Resultsmentioning
confidence: 99%
“…The most common pattern of nerve injury after knee dislocation is a CPN palsy. Tibial nerve injuries are rare 9 but have substantial consequences of both nerve-based and tendon transfer–based reconstructive options.…”
Section: Sports Medicine Perspectivementioning
confidence: 99%
“…Although operative reconstruction and rehabilitation lead to marked improvement in knee-specific measures of function, there is usually a lasting impact on quality of life. 9 The frequency of common peroneal nerve (CPN) injury after knee dislocation is estimated to occur in 25% of patients. 24 The functional deficits associated with CPN injury affect ambulation, with 35% of patients requiring use of an ankle-foot orthosis (AFO).…”
Section: Introductionmentioning
confidence: 99%